Microscopic and spectroscopic characterization of nutlets and mucilage of Ocimum basilicum and Thymus vulgaris - Alimpić Aradski, Ana; Pećinar, Ilinka; Janković, Smiljana; Marin, Petar D.; Pljevljakušić, Dejan; Dajić-Stevanović, Zora; Šavikin, Katarina; Duletić-Lauševič, Sonja (Acta herbologica, 2023)
Ocimum basilicum L. (basil) and Thymus vulgaris L. (thyme) are well-known medicinal plants from the Lamiaceae family. Although the micromorphological characteristics and mucilage production of basil and thyme fruits have already been partially studied, the aim of this work was to examine samples collected in Serbia. The results obtained by stereomicroscope and scanning electron microscopy showed that the nutlets of these species differ in size, shape, abscission scar, and ornamentation pattern. Although the nutlets of both species produced milky opaque mucilage with fibrils, the basil nutlets showed a faster and more abundant mucilage reaction. Also, this is first report on the evaluation of the chemical composition of nutlets and mucilage of two Lamiaceae species grown in Serbia using Raman microspectroscopy. Some differences were found between the investigated species with regard to the chemical profile of both nutlets and mucilage. The differences between the nutlets are mainly determined by the content of phenolic compounds, fatty acids and proteins. The examined nutlets are good sources of phenols, unsaturated fatty acids and polysaccharides. Raman spectroscopy seems to be a suitable technique for the analysis of this type of samples, as it allows the identification and spatial distribution of the plant metabolites.